Urbanidade : digressões entre universidade e cidade. Um estudo de caso dos espaços de fronteira do Campus de Santiago da Universidade de Aveiro, Portugal - Medeiros, Helen Maria Palmeira (2023)
This thesis is the result of a qualitative investigation of a single and exploratory case study that has as its object urbanity through the socio-spatial integration of the edge spaces of peripheral university campuses. The denomination of edge spaces refers to the open spaces located between the limits of the urban plot and the building, often resulting from obligations imposed by urban regulations. There is an understanding that these spaces could contribute to urbanity, by acting as mediators and amplifiers of public interaction spaces in cities that emerge in university surroundings, from the settlement of campuses. An ethnographic sensitivity is especially useful for the development of field research, in which attention was paid to situations of permanence and movements of humans in the open and edge spaces of the case study, the Campus of Santiago of the University of Aveiro (Aveiro, Portugal), as well as its immediate surroundings. These field activities served for us to explore the possibilities of establishing design principles for the edge spaces of university campuses. In parallel, it discusses the very notion of urbanity as a category of study and the validity of its association with the built environment of edge spaces. With the aid of the propositions of the Actor-Network Theory, it is considered that the urbanities are multiple experiences of and in the urban space, which tend to socio-spatial integration. Due to its relational and plural character, the pair urbanities-disurbanities is inseparable and represents a latency in each human and non-human actor. Finally, urbanity is dynamic and imponderable, therefore, the effort to identify the social actors and their collectives, the interests that drive them to action, as well as the eventual controversies they deal with may be helpful for an empirical approach of the various urbanities-disurbanities present in the university surroundings. Despite being digressive, the approximation of urbanities-disurbanities functions as a calibration of field research perceptions. Finally, despite digressive, the approach of the urbanities-disurbanities functions as a calibration to the field perceptions, in which a series of actors and mediations are invisible. Finally, although restricted to a single case study, the theoretical and methodological considerations presented here can be used for developping researches and analysis in existing cases in different contexts, including in Brazil.